The Blockchain Digital Health care use cases: Blockchain apllications (International Journal of Scientific Research and Management (IJSRM), 2023)
The blockchain is a powerful piece of technology that enables many individuals to access data and exchange it with one another in a protected environment. This presents a significant challenge in the field of digital health, where it is of the utmost importance to protect patient privacy and security but where it is impossible to improve care quality without improved patient data management across the entire healthcare system, and the ability to use analytics on patient data gathered at the population level. To summarise, blockchain technology has the potential to improve digital health by making it simpler and safer to communicate patient data across extremely decentralized healthcare systems. This would result in an overall improvement in digital health.